Caracterização fenotípica e molecular do painel brasileiro de genótipos de cana-de-açúcar - Barreto, Fernanda Zatti (Universidade Federal de São Carlos, 2016)
Sugarcane is a renewable source of energy and has potential for expansion. The economic importance of sugarcane is due to its use as raw material, mainly for the sugar and ethanol production and, more recently for the electricity generation from lignocellulosic residues. The genetic improvement of sugarcane is responsible for releasing more productive and resistant cultivars but, however, is a long process with high cost. Furthermore, the sugarcane is polyploid and often presents aneuploid, which makes the work of breeding programs even more hampered. Thus, the phenotypic and molecular knowledge of the access that are commonly used for the crosses to obtain segregating populations or that are part of genebanks of breeding programs is of extreme importance, because this knowledge may drive the improvement process and increases the chances of selecting superior cultivars that meet the demand of the sugarcane industry. In this work, a panel of 242 genotypes of sugarcane, which compose the Brazilian Panel of Sugarcane Genotypes (PBGCA), was planted in the Agricultural Sciences Center of the Federal University of São Carlos, at Araras-SP, in a completely randomized block design with four replications. We evakuated eight phenotypic traits of economic importance: stalk height (m), stalk diameter (mm), stalk number, total weight (kg), soluble solids content (ºBrix), juice sucrose content (POL%Caldo), cane sucrose content (POL%Cana) and fiber content (FIB%); and also the incidence of brown rust (Puccínia melanocephala) at field and the presence of the resistance gene of this disease (Bru1). The estimate of variance, genotypic correlation analysis and principal component analysis showed the genetic diversity of PBGCA, which has, for example, contrasting genotypes for sucrose content and fiber content. In addition, from all resistant accessions on the field to brown rust, 72.30% present the Bru1 gene, which is strongly associated with resistance. Phenotypic and molecular characterization of PBGCA showed to be an efficiently important guide for the breeding strategies and enables future studies of association between traits of economic importance and molecular markers in order to perform assisted selection in sugarcane.
Phenotypic and molecular characterization of the brazilian panel of sugarcane genotypes
Keywords: Cana-de-açúcar; Caracterização fenotípica e molecular; Painel brasileiro de genótipos de cana- de-açúcar; Sugarcane; Phenotypic and molecular characterization; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL